Consuming Probiotic Foods Copes with Stress in The Pandemic Era - zafira syafa; Fauziatul Khusna; Sania Rahmatika (Universitas Nahdlatul Ulama Surabaya, 2021)
One of the problems facing today is the Covid-19 pandemic. This problem has an impact on health, economic, social, religious, and psychological aspects. Psychological issues include anxiety and stress. The authors suggest consuming probiotic foods such as tempeh and yogurt to cope with stress Probiotics contain bacteria in the intestines having an essential role in brain function, stress,  and neurodevelopmental disorders. In addition, it has a beneficial effect on physical and psychological health.